Surface modification of TiO2 nanorod arrays with Ag3PO4 @ PANI nanoparticles for enhancing photoelectrochemical performance. (2019) - He, Rong; Gu, Xiuquan; Zhao, Yulong; Qiang, Yinghuai
In this work, Ag3 PO4 @PANI particles with a core/shell structure were deposited onto the oriented TiO2 nanorod arrays (NRAs) by a facile dipping route, in order to enhance the visible-light response as well as photoelectrochemical (PEC) performance of TiO2 samples. Furthermore, the crystal structure, morphology, and optical properties of the composites (TiO2 photoanodes) were evaluated by a number of techniques, including scanning and transmission electron microscopy (SEM, TEM), X-ray diffractometry (XRD) and UV-vis spectroscopy. Meanwhile, on/off photocurrent response, and impedance spectroscopy measurements as well as Mott-Schottky analysis were employed to make a characterization over TiO2 photoanodes before and after surface modification. A photocurrent density of 4.0 mA cm −2 is achieved at 0.0 V vs. saturated calomel electrode (SCE) under an illumination of 100 mW/cm 2, which is 2 times higher than that of pristine TiO2 photoanode measured under the same conditions. The performance improvement was mainly attributed to the enhanced visible-light response of TiO2 .